The Effect of Unemployment Insurance on Unemployment Duration and the Subsequent Employment Stability - Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2004)
This paper studies the effect of unemployment benefits on the unemployment and subsequent employment duration using individual data from the European Community Household Panel, for France, Germany, and the UK. The empirical analysis is based on a two-state mixed proportional hazard model allowing for flexible duration dependence and state specific unobserved heterogeneity. We find that recipients, relative to non-recipients, face lower exit rates from unemployment, while an additional month in unemployment increases their subsequent employment stability. This positive correlation between previous unemployment and subsequent employment duration for the recipients is statistically significant for the short-term unemployed in France and Germany. The results indicate that in these two countries, which provide more generous benefits relative to the UK, recipients who search for a longer period within the first year in unemployment obtain higher employment stability.
Keywords: C41; J64; J65; 330; unemployment insurance; unemployment duration; employment duration; duration analysis; Arbeitslosenversicherung; Arbeitslosigkeit; Dauer; Arbeitsplatzsicherung; Betriebszugehörigkeit; Schätzung; Grossbritannien; Deutschland; Frankreich